Estudo teórico de compostos de C6F5-corrol funcionalizados com hidrocarbonetos aromáticos para aplicações em terapia fotodinâmica - Rocha, Vinícius do Nascimento da (2021)
The oxygen singlet generation by molecules in photodynamic therapy (PDT) requires an electronic excitation by light absorption within a specific wavelength window, and a subsequent intersystem crossing transition to a triplet excited state that is at least 0.98 eV higher in energy than the singlet ground state. Tetrapyrrolic macrocycles, such as corrole, have been widely used in oxygen singlet generation for PDT. Suitable functionalization has also potentialized corroles as photosensitizers. In this contribution, time dependent functional theory (TDDFT) was used to determine the structural, electronic and spectroscopic properties as well as the spin-orbit coupling (SOC) matrix elements for possible intersystem crossing channels of the corrole macrocycles bound to different polycyclic aromatic hydrocarbon, namely C6F5phenyl, naphthyl, anthracenyl and pyrenyl. Our results show that light absorption at the therapeutic window involves mainly the corrole macrocycle unit. The most likely channel to the intersystem crossing process lead to a triplet excited state that satisfies the energy requirement for the oxygen singlet generation. The spin-orbit coupling (SOC) matrix elements associated with the intersystem crossing are connected with the carbonic rings of polycyclic aromatic hydrocarbons, and a correlation between the magnitude of the SOC matrix elements and the aromaticity of the carbonic rings is suggested. These results shows that the corrole macrocycles suitably functionalized with polycyclic aromatic hydrocarbons fulfill several criteria necessary to be used as good PDT photosensitizers.